Shallow water sponges along the south coast of Java, Indonesia - TRI ARYONO HADI; MUHAMMAD HAFIZT; HADIYANTO HADIYANTO; AGUS BUDIYANTO; RIKOH MANOGAR SIRINGORINGO (Biodiversitas Journal of Biological Diversity, 2018)
Hadi TA, Hafizt M, Hadiyanto, Budiyanto A, Siringoringo RM. 2018. Shallow water sponges along the south coast of Java, Indonesia. Biodiversitas 19: 535-543. Sponges are the most diverse benthic filter feeders, occupying many different types of marine habitat. The south coast of Java is one such marine habitat, very exposed to the open sea. This study investigated the sponge diversity as well as their morphological characters across the south coast of Java. The observations were carried out from 2011 to 2016 in four different locations, including Pamang Peuk, Gunungkidul, Prigi Bay and Bayuwangi. The study found 96 sponge species, from 15 orders, and described them in terms of nine morphological characters. The most common species included Spheciospongia inconstans, Stylissa massa, Callyspongia sp. and Cinachyrella australiensis, while the most common growth forms were massive and encrusting, accounting respectively for 34.4% and 28.1% of the total number of species. There was a significant difference in the number of species found between sub-tidal and intertidal habitats; subtidal sponges were approximately 50% more diverse than intertidal sponges. Apart from the habitat types, the number of sponges varied in relation to the longitude; east Java had more sponge species with more variations in morphology compared to central and west Java. Encrusting and globular growth forms were the most common characteristics of intertidal sponges in west and central Java, while other growth forms comprised the diverse characteristics of the subtidal sponges in the east Java. This baseline information is essential for management of marine biodiversity hotspots in taking decisions for marine life conservation, because the global trajectory of marine habitat degradation is predicted to rise.